Stearidonic acid improves eicosapentaenoic acid status: studies in humans and cultured hepatocytes - Seidel, Ulrike; Eberhardt, Katharina; Wiebel, Michelle; Luersen, Kai; Ipharraguerre, Ignacio R.; Haegele, Franziska A.; Winterhalter, Peter; Bosy-Westphal, Anja; Schebb, Nils Helge; Rimbach, Gerald (Frontiers in Nutrition, 2024)
Background: Ahiflower oil from the seeds of Buglossoides arvensis is rich in α-linolenic acid (ALA) and stearidonic acid (SDA). ALA and SDA are potential precursor fatty acids for the endogenous synthesis of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which are n3-long chain polyunsaturated fatty acids (n3-LC-PUFAS), in humans. Since taurine, an amino sulfonic acid, is often associated with tissues rich in n3-LC-PUFAS (e.g. in fatty fish, human retina), taurine may play a role in EPA-and DHA-metabolism. Objective: To examine the capacity of the plant-derived precursor fatty acids (ALA and SDA) and of the potential fatty acid metabolism modulator taurine to increase n3-LC-PUFAS and their respective oxylipins in human plasma and cultivated hepatocytes (HepG2 cells). Methods: In a monocentric, randomized crossover study 29 healthy male volunteers received three sequential interventions, namely ahiflower oil (9 g/day), taurine (1.5 g/day) and ahiflower oil (9 g/day) + taurine (1.5 g/day) for twenty days. In addition, cultivated HepG2 cells were treated with isolated fatty acids ALA, SDA, EPA, DHA as well as taurine alone or together with SDA. Results: Oral ahiflower oil intake significantly improved plasma EPA levels (0.2 vs. 0.6% of total fatty acid methyl esters (FAMES)) in humans, whereas DHA levels were unaffected by treatments. EPA-levels in SDA-treated HepG2 cells were 65% higher (5.1 vs. 3.0% of total FAMES) than those in ALA-treated cells. Taurine did not affect fatty acid profiles in human plasma in vivo or in HepG2 cells in vitro. SDA-rich ahiflower oil and isolated SDA led to an increase in EPA-derived oxylipins in humans and in HepG2 cells, respectively. Conclusion: The consumption of ahiflower oil improves the circulating levels of EPA and EPAderived oxylipins in humans. In cultivated hepatocytes, EPA and EPA-derived oxylipins are more effectively increased by SDA than ALA.